2004
DOI: 10.3748/wjg.v10.i23.3399
|View full text |Cite
|
Sign up to set email alerts
|

Transabdominal ultrasonography in preoperative staging of gastric cancer

Abstract: Transabdominal US is useful for preoperative staging in gastric cancer, although it is difficult to differentiate benign from malignant lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 35 publications
0
33
0
2
Order By: Relevance
“…These results indicated that gastric cancers that were detected using US were at a more advanced stage compared with those that were not detectable using US. The advancement of gastric cancer is represented with T staging (23), which can be evaluated using transabdominal US with patients drinking water prior to the scan, or using endoscopic US (24,25). In the current study, it was difficult to evaluate pT staging using US as the patients did not consume water prior to screening, and thus pT staging was evaluated subsequent to surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that gastric cancers that were detected using US were at a more advanced stage compared with those that were not detectable using US. The advancement of gastric cancer is represented with T staging (23), which can be evaluated using transabdominal US with patients drinking water prior to the scan, or using endoscopic US (24,25). In the current study, it was difficult to evaluate pT staging using US as the patients did not consume water prior to screening, and thus pT staging was evaluated subsequent to surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…• The sensitivity and specifi city of AUS for the detection of LN metastasis varied between 12.2% and [33] 2004 − − − − − + − + + + − − − 2 2 31 Lee et al [42] 2001 − − − + + + − + + + + + + 4 5 69 Düx et al [53] 1997 + − + + − + − + + − + + + 5 4 69 Kim et al [54] 1997 − − + − + + − − + + − + + 3 4 54 Stell et al [57] 1996 − − − − + − − + + + + + + 2 5 54 EUS Lok et al [17] 2008 − − − − + − − − + + + − + 1 4 38 Bentrem et al [19] 2007 + − − + + + − + + − + + + 5 4 69 Tan et al [20] 2007 − − + + + + − + + + − − − 5 2 54 Arocena et al [24] 2006 + − − − + + − − + + − + + 3 4 54 Ganpathi et al [25] 2006 − − − − + + − + + + + − + 3 4 54 Tsendsuren et al [26] 2006 − − − + + + − + + + − − − 4 2 46 Ang et al [27] 2006 + − − − + + − − + − − + − 3 2 38 Potrc et al [29] 2006 + + − + + + − + + − − + + 6 3 69 Polkowski et al [34] 2004 + − − − + + − + + + + + + 4 5 69 Bhandari et al [35] 2004 + − − − + + − + + + − − + 4 3 54 Javaid et al [36] 2004 − − − + + + − + + + − + − 4 3 54 Habermann et al [37] 2004 + − − + + + − + + + + − + 5 4 69 Xi et al [40] 2003 − − − + + + − + + + − + − 4 3 54 Chen et al [41] 2002 − − + + + + − + + + + + + 5 5 77 Willis et al [43] 2000 + − − + + + − + + + + + − 5 4 69 Tseng et al [44] 2000 − − − + + + − + + + − + + 4 4 62 Mancino et al [46] 2000 − − − + + + − + + + − − − 4 2 46 Akahoshi et al [48] 1998 + − − − + + − + + + + + − 4 4 62 Hunerbein et al [49] 1998 + − − − + + − + + − − − + 4 2 46 Wang et al [50] 1998 + − − + + + − + + + − + − 5 3 62 Hamada et al [52] 1997 − − − + + + − + + + − − − 4 2 46 Hunerbein et al [55] 1996 + − − − − + − + + − + + − 3 3 46 François et al [56] 1996 + − − − + + − + + + − + − 4 3 54 Perng et al [58] 1996 + − − + + − − − + + − + − 3 3 46 Smith et al [60] 1993 − − − + + + − + + − − − + 4 2 46 Ziegler et al [61] 1993...…”
Section: Staging Performanceunclassified
“…We included only 2 studies that reported pre-operative T staging values (Appendix 1 of the electronic supplementary material), one of which had fair agreement (j, 95% confidence interval [CI]: 0.40, 0.20-0.60) and another with substantial agreement (0.66, 0.55-0.77). This variation may be explained by the difficulty in staging tumors found in the gastric fundus and greater curvature [7,8,42,43], as well as the highly subjective nature of AUS staging and thus its strong operator dependence [42,43].…”
Section: Evaluation Of T Stagingmentioning
confidence: 99%
“…Electronic literature searches were conducted using Medline and Embase from January 1, 1998 [42,43]. b Adapted from [28,53].…”
Section: Data Sourcesmentioning
confidence: 99%